A modified technique for making putty-wash two-step impression - Sunil Kumar Mishra; Puja Hazari; Ramesh Chowdhary; Shail Kumari (Wolters Kluwer Medknow Publications, 2017)
Background: If the impression thickness is uniform, stock trays can also give a better result when compared to custom trays. Purpose: This study aimed to obtain a uniform thickness impression with a modified putty-wash two-step technique. Materials and Methods: A chairside method of putty-wash two-step impression in a stock tray was made utilizing a wax spacer. Results: A uniform thickness impression was obtained in stock tray in quick time. Conclusion: The current article has given the options of using wax as spacer for making putty wash two step impressions for the fabrication of tooth-supported fixed restorations. Further research is required to find whether there is any dimensional inaccuracy caused in restorations due to usage of wax as a spacer.